Exploring the relationship between novel measurements of abdominal obesity and psoriasis: a cross-sectional study from the NHANES database - Hongshan Liu; Jianing Yuan; Yuxin Ma; Jingchen Liang; Fangcun Li; Weihui Zeng; Yanting Liu (Eating and Weight Disorders)
Abstract Background Psoriasis is a chronic skin disease affecting millions of people, with obesity being a common comorbidity. Many studies suggest that obesity may influence the onset and treatment efficacy of psoriasis. Currently, increasing evidence indicates that abdominal obesity is associated with various metabolic diseases, but research on the relationship between abdominal obesity and psoriasis remains limited. This study uses advanced obesity indicators such as the conicity index and body roundness index to explore the association between abdominal obesity and psoriasis. Methods This study is a cross-sectional analysis that uses univariate regression analysis and weighted multivariable logistic regression to investigate the relationship between conicity index, android percent fat, body roundness index, and psoriasis. Additionally, restricted cubic spline analysis was performed to explore the nonlinear association between these indicators and psoriasis. Subgroup analysis and interaction tests were also conducted. Results A total of 4873 participants were included in this study. After adjusting for confounding variables, the results showed a positive correlation between conicity index, android percent fat, body roundness index, and the risk of psoriasis. When conicity index, android percent fat, and body roundness index were converted into quartiles (Q1–Q4), the risk of psoriasis in the Q4 group was significantly higher compared to the Q1 group (conicity index: p = 0.032, android percent fat: p = 0.020, body roundness index: p = 0.003). In the subgroup analysis and interaction tests, no significant interaction between the conicity index, body roundness index, and the association with psoriasis was found (p > 0.05). The results only suggest that the poverty income ratio (PIR), marital status, and alcohol consumption may influence the relationship between android percent fat and psoriasis. In addition, subgroup analysis based on age shows that the association between abdominal obesity and psoriasis is more significant in the population over 40 years old. Conclusions After adjusting for covariates, the study found that three abdominal obesity indicators—conicity index, android percentage fat, and body roundness index—are positively correlated with psoriasis risk, suggesting that the association between abdominal obesity and psoriasis as a comorbidity is more likely to occur, emphasizing the clinical significance of this link. Level of evidence Level III, Evidence obtained from well-designed cohort or case–control analytic studies.